Strongly linearly polarized low threshold lasing of all organic photonic quasicrystals - Yang, H. Z. (2013)
Lasing is obtained from a two-dimensional (2D) Penrose photonic quasicrystal made of a low index contrast material of holographic polymer dispersed liquid crystals (H-PDLCs) that enables a substantial reduction in the optical pumping threshold. This lasing architecture further allows for excellent linear polarization characteristics as well as wide directional dependence. The pumping threshold is fivefold lower than that obtained from the 2D defect-free photonic crystals fabricated under similar conditions. These properties make H-PDLC photonic quasicrystal promising for a new type of all organic miniature lasers.